Frailty is associated with worse outcomes in non-ST-segment elevation acute coronary syndromes: Insights from the TaRgeted platelet Inhibition to cLarify the Optimal strateGy to medicallY manage Acute Coronary Syndromes (TRILOGY ACS) trial. Issue 3 (1st June 2016) - White, Harvey D; Westerhout, Cynthia M; Alexander, Karen P; Roe, Matthew T; Winters, Kenneth J; Cyr, Derek D; Fox, Keith A A; Prabhakaran, Dorairaj; Hochman, Judith S; Armstrong, Paul W; Ohman, E Magnus; ,
Abstract: Aims: Little is known regarding consequences of frailty in patients with acute coronary syndrome (ACS). We assessed the associations of frailty and outcomes in ACS patients who were participating in a clinical trial. Methods and results: The TaRgeted platelet Inhibition to cLarify the Optimal strateGy to medicallY manage Acute Coronary Syndromes (TRILOGY ACS) trial randomized 9326 patients planned for medical management to prasugrel or clopidogrel. The primary endpoint was a composite of cardiovascular death, myocardial infarction (MI), or stroke over a period of 30 months. A frailty score based upon the Fried score was self-reported at baseline in patients aged ⩾65 years. Five frailty questions were recorded for 4996/5102 (97.9%) patients: 72.3% were classified as not-frail (0 items), 23.0% as pre-frail (1–2 items), and 4.7% as frail (⩾3 items). Increasing frailty score was associated with older age, diabetes, and higher Global Registry of Acute Coronary Events (GRACE) scores. Frailty was associated with a higher unadjusted incidence of the primary endpoint (pre-frail vs not-frail: 29.2% vs 23.1%; hazard ratio [HR]: 1.39; 95% confidence interval [CI]: 1.19–1.61; p <0.001; frail vs not-frail: 39.7% vs 23.1%; HR: 1.76; 95% CI: 1.36–2.28; p <0.001), and all-cause mortality (pre-frail vs not-frail: 21.7% vs 15.0%; HR: 1.45; 95% CI: 1.22–1.73; p <0.001; frail vs not-frail: 30.2% vs 15.0%; HR: 1.98; 95% CI: 1.47–2.68; p <0.001). After adjustment for baseline characteristics and GRACE covariates, frailty remained independently associated with the primary endpoint: pre-frail vs not-frail, HR: 1.33; 95% CI: 1.15–1.54; p <0.001; frail vs not-frail, HR: 1.52; 95% CI: 1.18–1.98; p =0.002. There was no association of frailty with bleeding. Conclusion: Frailty is associated with the composite of cardiovascular death, MI, or stroke. Frailty assessment contributes to risk prediction and adds to the GRACE score.